MEDICALTOURISM IN INDIA:TRENDSAND COMPETITIVE ADVANTAGES - CHAUDHARY, MANJULA (ITB Journal Publisher, LPPM ITB, 2009)
With globalization and spread of Internet the world is becoming a big mart with consumers shopping for best value of money across political boundaries. This is opening a global customer base for the product and service providers. Developing countries too are using this opportunity to create their own competitive advantages. Information Technology sector is already witnessing the power of competitive and differential advantage of developing nations and healthcare is emerging as another potential area. The health services at reasonable prices - at least in comparison to the developed countries, are attracting large number of people from across the globe to a few select destinations. Globally this market is estimated to be to the tune of US 40 billion growing at the rate of 15 per cent per annum. India is the new entrant in the field that has seen an upward trend in attracting the foreign tourists for medical purposes in the recent years and is counted among potential frontrunners. While on the one hand its medical tourism is lauded for its revenue generation and service excellence capabilities, on the other hand doubts are also being raised about a number of related issues pertaining to real advantages to patients as well as service providers. This paper makes an assessment of the existing trends, infrastructure required for medical tourism and evaluation of the advantages that India possesses besides taking stock of the trends in medical tourism at the global level.